CARBON ABSORPTION CAPABILITY THE WATERS IN THE RUPAT STRAIT OF RIAU PROVINCE - Siti Ramlah Hasibuan; Rifardi Rifardi; Sampe Harahap (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
The purpose of this study isto analyze the uptake of carbon in polluted waters and unpolluted based on suspended sediment concentration in Rupat Strait. This study used multivariate statistics of Principle Component Analysis (PCA) and regression analysis to clarity the relationship between suspended sediments and primary productivity with carbon uptake. The results indicate that carbon uptake in polluted waters range from 0.023-0.026 tonC/m2/year and unpolluted ranged from 0.034- 0.038 tonC/m2/year. PCA analysis shows that the two main axes (F1 and F2) can represent 82.26% of the total diversity of distribution, indicate the contribution of F1 is 70.08% and F2 is 12.18%. The relationship between total suspended sediment with carbon uptake clearly show if total suspended sediment is higher, the carbon uptake will be lower. On the other hand the relationship between primary productivity and carbon uptake, indicate abundance of primary productivity, the carbon uptake will behigher.